Boosting Performance on an Evaluative Math Test: Goal Activation vs Self-Affirmation - Wieland, Alice M.; Burnham, Thomas A. (Psychological Reports, 2016)
This study compared the effectiveness of goal activation versus self-affirmation and a control condition as interventions for increasing performance on an evaluative task (a difficult math test; N = 78; M age = 20.3 yr., SD = 1.9). Although there has been much recent literature on the effects of activating goals, the existing literature does not examine possible spillover effects of activating goals on performance tasks. Results indicated that goal activation resulted in significant performance enhancements over both the self-affirmation and control conditions, while self-affirmation did not improve performance significantly relative to the control condition. Additionally, interest in the task, as a cue for self-regulatory resources, mediated the effect of goal activation on increased performance.
Keywords: dept.mgt

Designing Entrepreneurship Experiments: A Review, Typology, and Research Agenda - Hsu, Dan K.; Simmons, Sharon A.; Wieland, Alice M. (Organizational Research Methods, 2017)
This article discusses the current and potential application of experimental methods to the study of entrepreneurship phenomena. Drawing on a review of experimental studies in entrepreneurship research, we discuss the advantages and disadvantages of experimental research designs for entrepreneurship research as a primer for those interested but not overly familiar with these methods. To advance research agendas and theory in the field, we introduce a typology of experimental manipulations that highlight alternative design choices based on the nature of their participant impact and realism of context. Finally, we provide an overview of areas of opportunity within the entrepreneurship literature for application of methods best suited to provide greater insight into the causal mechanisms at play.
Keywords: dept.mgt; peer-reviewed